Severity of target spot and gas-exchange in tomato cultivated under colored films - Anna Carla de Castro Paixão; Rosalee Albuquerque Coelho Netto; Ricardo Antonio Marenco; Edna Dora Martins; Newman Luz (Revista Ceres, 2022)
ABSTRACT The tomato target spot caused by Corynespora cassiicola may have an important economic impact on tomato production in tropical regions. The objective of this work was to study the effect of different colored plastic films on tomato target spot severity, gas-exchange, and fruit yield. Disease severity, photosynthetic rate, stomatal conductance, transpiration rate, relative chlorophyll content and fruit yield were evaluated in tomato, grown in individual mini-greenhouses covered with transparent plastic films of different colors (clear, red, blue, green, and yellow). At the beginning of the target spot epidemic, the plants under red and blue covers had lower leaf disease infection than those under other colored films (p = 0.013). However, as the disease progressed over time, the effect of the colored films on disease severity become non-significant (p = 0.82), and at the end of the experimental period, the target spot infection was about 70% in all treatments. Photosynthetic rates, stomatal conductance, and transpiration rate were not affected by the plastic film covers; neither the fruit number or fruit production. This study showed that colored films may reduce the infection by target spot, but only in the early stages of disease development (up to ~2% severity).